The Hypoglycaemic and Chemical Studies of Parkia Speciosa, Hassk - Jamaludin, Fathaiya (1991)
The administration of the chloro form extracts of Parkia speciosa (petai papan) to alloxan- treated diabeticrats produced a significant depression in blood glucose levels . Other solvent extracts failed to induce any reduction in the blood glucose levels of the diabetic animals. In normal rats serum glucose levels we re not changed after the administration of chloroform extracats (400 mg/kg body weight) comparable to those administered with saline solution . The determination of dose - response relations hip of fresh and g round seeds and empty pods showed that the minimum effective dose of raw materils necessary to produce a significant (p <0.0001) decrease in serum glucose concentration was 25 mg/kg body weight.